How Operating Expense And Revenue Budgets Influence Financial Performance: An Analysis Through Return On Assets - Lis Setyowati; Nuryadi Nuryadi; Dian Sari; Abu Darim; Andrik Gastri Widjatmiko; Ony Thoyib Hadiwijaya (INVENTORY: JURNAL AKUNTANSI, 2025)
The purpose of the study was to determine the effect of operating cost budgets and revenue budgets on financial performance based on the return on assets (ROA) ratio at PT Wijaya Tirta Makmur, there are three variables, namely operational cost budgets (X1), revenue budgets (X2), and ROA (Y). The abstract contains a brief description of the purpose: describes the objectives and hypotheses of the research. Methods: describes the essential features of the research design, data, and analysis. It may include the sample size, geographic location, demographics, variables, controls, conditions, tests, descriptions of research design, details of sampling techniques, and data gathering procedures. Results: describes the key findings of the study, including experimental, correlational, or theoretical results. It may also provide a brief explanation of the results. Implications: show how the results connect to policy and practice and provide suggestions for follow-up, future studies, or further analysis. Additional materials: notes the number of references, tables, graphs, exhibits, test instruments, appendixes, or other supplemental materials in the paper. Also, the abstract must be written in a single paragraph in English, max 250 words. With the verification method, the sample used is the company's Return on Assets (ROA), operational cost budgets and revenues in the 2016-2020 period. Using secondary data, the data collection technique is a documentation technique. The data analysis technique used multiple linear regression analysis with SPSS version 16 program. The conclusion of this study is that partially the operational cost budget has no effect on ROA but the income budget has an effect on ROA. Simultaneously both have an effect on ROA. Shows the results of the R square value of 0.984.